2015
DOI: 10.1002/app.41911
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties, cure characteristics, and morphology of acrylonitrile‐based nanorubber modified epoxy

Abstract: This article investigates the effects of nano carboxylic acrylonitrile butadiene rubber (CNBR-NP) and nano acrylonitrile butadiene rubber (NBR-NP) on the rheological properties and cure characteristics of epoxy. Dynamic mechanical behavior of carbon fiber reinforced polymer composites (CFRP) with the nanorubber-modified matrices was also studied. Rheological study showed that NBR-NP blends attained lower viscosity in comparison to CNBR-NP blends and both systems exhibited shear-thinning behavior. Scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The morphology and the change in stoichiometry of the matrix with the nanorubber dispersion can affect the interlaminar shear stiffness and strength properties. However, we have proved with dynamic mechanical analysis that the change in the degree of crosslinking with the nanorubber modification is insignificant [14]. To summarise, the consistent decrease of the APS value with the nanorubber concentration may be explained by the lower quality of the laminates with high void content, and by the low stiffness of the nanorubber particles that cause a reduction in the stiffness of the resin.…”
Section: Failure Modes Of the Short Beam Shear Specimensmentioning
confidence: 72%
See 4 more Smart Citations
“…The morphology and the change in stoichiometry of the matrix with the nanorubber dispersion can affect the interlaminar shear stiffness and strength properties. However, we have proved with dynamic mechanical analysis that the change in the degree of crosslinking with the nanorubber modification is insignificant [14]. To summarise, the consistent decrease of the APS value with the nanorubber concentration may be explained by the lower quality of the laminates with high void content, and by the low stiffness of the nanorubber particles that cause a reduction in the stiffness of the resin.…”
Section: Failure Modes Of the Short Beam Shear Specimensmentioning
confidence: 72%
“…In our previous work, the effect of acrylonitrilebased nanorubbers on the cure kinetics, physical properties and the processing of epoxy resin were studied. We have showed that the acrylonitrile based nanorubber materials do not increase the viscosity of the specific epoxy resin beyond its processing limits; neither do they affect the T g of the system [14]. Hence, previous work deals with the properties of the nanorubber-toughened matrix resin only, and the current work represents a continuation, studying the mechanical properties of the CFRP composites with the nanorubber toughened epoxy resin matrices.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations